A mathematician's apology - Hardy, G. H. [ (Godfrey Harold)] , 1877-1947; Snow, C. P. [ (Charles Percy)] , 1905-1980 (Canto classics, 2012)
A unique account of the fascination of mathematics and of one of its most compelling exponents in modern times